Estudo de frequências alélicas de 15 STRs autossômicos na população paraibana - Castro, Sarah Gurgel de (2014)
Human identification is based on analyzing DNA through present throughout the genome molecular markers. These markers are transmitted from parents to offspring by heredity. STR markers are currently the most commonly used genetic markers in Forensic Genetics due to their high polymorphism, high reproducibility, possibility of being amplified by PCR in multiple copies in a single reaction, and minute quantities of DNA (1ng). The DNA test that allows individualization of the people is essential tool to the solution of forensic human identification cases, sex crimes, crime scenes (including or excluding suspects), mass disasters, and its result is presented in statistical calculations that consider allele frequency of markers used. So it is important to know the allele frequencies presented in the regional population so that the results are the most reliable possible. In this study , 15 autossomal markers (loci) STR or microsatellite (CSF1PO, D13S317, D16S539, D18S51, D19S433, D21S11, D2S1338, D3S1358, D5S818, D7S820, D8S1179, FGA, TH01, and VWA TPOX) were studied in 766 unrelated individuals paraibanos, demonstrating a tri population - hybrid formed Africans (25.86 %), Amerindian (6.81 %) and Europeans (67.33 %). The most informative were D21S11 and FGA, and were less informative TPOX, D7S820 and D13S317. The results are important for a database with allele frequencies found in Paraiba population can serve as a useful basis for calculating forensic practice in the State of Paraíba.